"That's the way my Wednesdays always go": reverse-order instructions insufficient to mitigate schema-consistent errors in alibi generation. Issue 3 (9th July 2021) - Eastwood, Joseph; Snow, Mark D.; Freedman, Stuart
Abstract : Purpose: The purpose of this study was to assess the ability of innocent suspects to produce accurate alibis, as well as to identify procedures police interviewers can use to increase the probability of generating accurate alibis. Design/methodology/approach: In Study 1, 54 university students had a lecture (target event) end at either the normal time (schema group) or 25 min early (non-schema group) and then attempted to generate an alibi for the target event after either a short, moderate or long delay. In Study 2, 20 students had a lecture end 25 min early and underwent an interview regarding their whereabouts using a reverse-order interview technique designed to disrupt schema usage. Findings: Results from Study 1 suggested that participants relied on schemas to generate their alibis, which led to false alibis for the non-schema group, and this reliance was more pronounced as the delay between event and recall increased. In Study 2, all but one participant produced a false alibi, suggesting reverse order is ineffective in increasing accurate recall in alibi situations. Practical implications: Results from the two studies revealed that people can produce false alibis easily in mock police interviews – a finding that appears to result from the reliance on schemas. These findings highlight the relative ease with which innocent individuals can produce false alibis. Further research, specific to the alibi generation process, is needed to give police interviewers the tools to produce more accurate and detailed alibis. Originality/value: This research provides additional evidence regarding the role of schemas in alibi generation. Contrary to findings from the eyewitness area, reverse-order instructions failed to disrupt schema reliance and do not appear to be an effective alibi-elicitation technique.